2022
DOI: 10.1093/plphys/kiac226
|View full text |Cite
|
Sign up to set email alerts
|

The circadian clock mutantlhy cca1 elf3paces starch mobilization to dawn despite severely disrupted circadian clock function

Abstract: Many plants, including Arabidopsis (Arabidopsis thaliana), accumulate starch in the daytime and remobilize it to support maintenance and growth at night. Starch accumulation is increased when carbon is in short supply, for example, in short photoperiods. Mobilization is paced to exhaust starch around dawn, as anticipated by the circadian clock. This diel pattern of turnover is largely robust against loss of day, dawn, dusk, or evening clock components. Here, we investigated diel starch turnover in the triple c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Recently, a series of carefully designed experiments showed that the percentage of photoassimilates dedicated to starch is dependent on daylength but independent of light intensity and the daily light integral, a so-called truly photoperiodic process that responds to the duration of the light rather than the photon flux intensity ( 89 ). This was subsequently shown to be under the control of the circadian clock when a cca1 lhy elf3 triple mutant was unable to increase photoassimilate partitioning to starch in SDs, but maintained the ability to adjust starch degradation to accommodate the long night ( 3 ). This indicates that there are separate daylength measurement systems to alter starch synthesis and degradation rates in response to changing photoperiods.…”
Section: Photoperiodic Control Of Developmentmentioning
confidence: 99%
“…Recently, a series of carefully designed experiments showed that the percentage of photoassimilates dedicated to starch is dependent on daylength but independent of light intensity and the daily light integral, a so-called truly photoperiodic process that responds to the duration of the light rather than the photon flux intensity ( 89 ). This was subsequently shown to be under the control of the circadian clock when a cca1 lhy elf3 triple mutant was unable to increase photoassimilate partitioning to starch in SDs, but maintained the ability to adjust starch degradation to accommodate the long night ( 3 ). This indicates that there are separate daylength measurement systems to alter starch synthesis and degradation rates in response to changing photoperiods.…”
Section: Photoperiodic Control Of Developmentmentioning
confidence: 99%
“…By contrast, the long period mutant pseudo-response regulator 7/9 ( prr7/9 ) (a free-running period of 29.4 h [ 10 ]) delays the onset of starch degradation, resulting in continuous starch accumulation throughout the day [ 9 ]. More recently, the use of a triple mutant with impaired clock functions, cca1/lhy/elf3 , which also lacks the EARLY FLOWERING3 ( ELF3 ), unravelled that plants with a dysfunctional clock are unable to adjust the starch accumulation rate, but they can still adjust the pace of starch degradation [ 11 ]. This means that the circadian oscillator might operate in a semi-autonomous mode to integrate temporal information in a complex network [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the use of a triple mutant with impaired clock functions, cca1/lhy/elf3 , which also lacks the EARLY FLOWERING3 ( ELF3 ), unravelled that plants with a dysfunctional clock are unable to adjust the starch accumulation rate, but they can still adjust the pace of starch degradation [ 11 ]. This means that the circadian oscillator might operate in a semi-autonomous mode to integrate temporal information in a complex network [ 11 ].…”
Section: Introductionmentioning
confidence: 99%